Current Prevention of COVID-19: Natural Products and Herbal Medicine - Huang, Junqing; Tao, Gabriel; Liu, Jingwen; Cai, Junming; Huang, Zhongyu; Chen, Jia-xu (Frontiers in Pharmacology, 2020)
Starting from December 2019, novel coronavirus disease 2019 (COVID-19) pandemic has caused tremendous economic loss and unprecedented health crisis across the globe. While the development of cure is at full speed, less attention and fewer effort have been spent on the prevention of this rapidly spreading respiratory infectious disease. Although so far, several vaccine candidates have advanced into clinical trials, limited data have been released regarding the vaccine efficacy and safety in human, not mention the long-term effectiveness of those vaccines remain as open question yet. Natural products and herbal medicines have been historically used for acute respiratory infection and generally show acceptable toxicity. The favorable stability for oral formulation and ease of scaling up manufacture make it ideal candidate for prophylactic. Hereby, we summarized the most recent advance in SARS-CoV-2 prevention including vaccine development as well as experimental prophylactics. Mainly, we reviewed the natural products showing inhibitory effect on human coronavirus, and discussed the herbal medicines lately used for COVID-19, especially focused on the herbal products already approved by regulatory agency with identifiable patent number. We demonstrated that to fill in the response gap between appropriate treatment and commercially available vaccine, repurposing natural products and herbal medicines as prophylactic will be a vigorous approach to stop or at least slow down SARS-CoV-2 transmission. In the interest of public health, this will lend health officials better control on the current pandemic.